2020
DOI: 10.2147/prom.s243678
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Relationship Between Health Literacy Level and Self-Care Behaviors in Patients with Diabetes</p>

Abstract: Background: The most important factor in controlling diabetes is self-care behaviors; improving self-care behaviors is the first step in helping patients to better control and manage their diseases and health literacy is recognized as a vital and important indicator of outcomes and costs in healthcare. Therefore, the effectiveness of health-care systems requires that people have the desirable health literacy level. Therefore, this research intended to study the relationship between health literacy levels in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 15 publications
(17 reference statements)
3
25
0
1
Order By: Relevance
“…The results can be explained by a fact that self-care activities, such as the frequency of blood glucose testing and the frequency of insulin administration, many times go hand in hand and both are important parts of T2DM therapy. The findings of the study are in line with the previous researches according to which diabetes therapy and self-management can be successful only if patients follow complex treatment plans of diabetes therapy [25,32,68]. In sum, it seems that one of the important key factors for successful diabetes self-care are diabetes numeracy skills which could help patients to cope with the consequences of a chronic illness, increase patients' understanding and awareness of their chronic disease and help facilitate their engagement in diabetes self-management [19,26].…”
Section: Discussionsupporting
confidence: 87%
“…The results can be explained by a fact that self-care activities, such as the frequency of blood glucose testing and the frequency of insulin administration, many times go hand in hand and both are important parts of T2DM therapy. The findings of the study are in line with the previous researches according to which diabetes therapy and self-management can be successful only if patients follow complex treatment plans of diabetes therapy [25,32,68]. In sum, it seems that one of the important key factors for successful diabetes self-care are diabetes numeracy skills which could help patients to cope with the consequences of a chronic illness, increase patients' understanding and awareness of their chronic disease and help facilitate their engagement in diabetes self-management [19,26].…”
Section: Discussionsupporting
confidence: 87%
“…This finding was consistent with a study conducted in Iran where low health literacy was associated with poor diabetes self-care practices, 84 and the patients with lower health literacy did not adequately understand instructions to perform diabetes self-care. 85 , 86 This lower literacy might be that no best strategy was implemented to enhance patients’ health literacy levels. In addition, there was no well-designed diabetes patients’ education that considers literacy, culture, languages to enhance their literacy levels through multiple strategies, including video-assisted education, which might enhance self-care practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between health literacy and health behaviors remains unclear. Although most studies have identified the association between health literacy and health behaviors, such as diabetes management, 22,23 few studies have been conducted on this topic during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%